Pretax Payroll Deduction for Parking? An Illustrating Example - Lei, Adam Y.C.; Li, Huihua (Journal of Accounting and Finance, 2023)
Unlike the pretax payroll deductions common for insurance premiums, employees paying for parking may have the option to use either pretax or after-tax payroll deduction. The pretax deduction lowers the Social Security earnings, which could reduce the Social Security retirement benefit to an individual. This paper quantifies the adverse effect the pretax deduction may have, using a simplified example of a university faculty member in Texas. We conclude that choosing the pretax payroll deduction for parking is advisable for most faculty members. Our conclusion remains the same considering early and delayed retirement, besides retirement at the full retirement age.